Teacher Quality and Sorting across Traditional Public and Charter Schools in the Detroit Metropolitan Region - Michael F. Addonizio; C. Philip Kearney; Marytza A. Gawlik (Educational Considerations, 2015)
In the quest to raise student achievement in low-performing urban schools, researchers often point to the central importance of recruitment and retention of a high quality teacher workforce.
Keywords: achievement; metropolitan; Teacher Quality; Research; certified teachers; substitute teachers; Statistical Analysis; public schools; recommendations